THE ORIGIN OF THE CONCEPT OF STYLE IN EUROPEAN MUSICAL THINKING - GARAZ, Oleg (Studia Universitatis Babes-Bolyai Musica, 2022)
Essentially, the emergence of the concept of style in European musical thinking is the consequence of the shift produced at the end of the Renaissance. The trend towards the simplification of language and musical expression and the subordination of both to the notional-poetic discourse determines the unimaginable: the hegemony of rhetoric and, implicitly, of style as a rhetorical sub-category having the function of organizing and controlling musical suggestiveness – the taxonomy of musically expressible emotions. It is also during the period of the musical Baroque that the practical insertion of the concept of style begins by cohabiting with the idea of genre in all its three forms: as a specific habitat for the performance of the musical act, as a composition coefficient and equally as a type of ethos. This confusion will persist for the entire period of use of the concept of style, which gradually fades as the insertion of postmodernism gathers momentum. As a tool for functional and semantic dislocation, style also acts in relation to the term canon, the only value reference until the shift from the mathematical-cosmic quadrivium to the discursive-philological trivium (the Del Bene moment, 1586). Apart from taking over the attributions from the concept of genre, style also claims the function of canon as the exclusive value reference. Starting with the Baroque, we already speak of the stylistic canon. The complete absorption of the canonical function by style takes place during the Viennese Classicism, when style becomes a personalizing-biological reference, attached to the musical thinking of a prominent personality (Wilhelm von Lenz, Beethoven et ses trois styles, 1855). Musical Romanticism raises the understanding of style to the level of an almost absolute exclusivity, on a par with the transcendentalism displayed by the genius-musician (the Liszt-Wagner paradigm). The dissipation of Romanticism determines the return to the identification through ethos: verism, expressionism, impressionism-symbolism and naturalism, so that it is only during the first musical modernism (1900-1914) that we witness the return to the purely technical Renaissance acceptance: the atonal style, during the second modernism (1918-1939) – the dodecaphonic style, the serial style, and further, during the third modernism (1946-1968) – the style of stochastic music, the style of aleatoric music, the minimalist style etc. The uselessness of the concept of style as a procedure of identification through differentiation (Boris Asafiev) and obviously as a meta-narrative is already revealed in musical postmodernism, with all the three anti-metanarrative “ideologies” of postmodernism: the ideology of distrust, the ideology of the fragment and the ideology of recovery.